The Delay in The Diagnosis of Lung Cancer Due to Misdiagnosis as Pulmonary Tuberculosis - Jatu Aviani; Satria Maulana EH; Ita Haryatie; Farih Raharjo; Yusup Subagio Sutanto; Ana Rima Setijadi (Jurnal Respirologi Indonesia, 2017)
Background: Lung cancer and pulmonary tuberculosis (TB) are global health problem. Similarity of symptoms of both made misdiagnose of lung cancer as TB and treated with Anti Tuberculosis Treatment (ATT). Evaluation of ATT often inaccurate, causing late diagnosis of lung cancer. This study aimed is to determine the lung cancer percentage with delayed diagnosis due giving of ATT for >1 month. Methods: A prospective descriptive study was performed from January 2014-February 2016 in Dr. Moewardi Hospital, Surakarta taken from the patient's medical record. Results: As much 293 patients with lung cancer consisted of 188 males (64.4%) and 105 females (35.8%) with the average age was 57 years old. The types of the lung cancer were non-small cell lung carcinoma (NSCLC) consisted of adenocarcinoma 195 subjects (66.6%), squamous cell carcinoma 65 subjects (22.2%), large cell carcinoma 23 subjects (7.8%) and neuroendocrine carcinoma 4 subjects (1.4%). The stages of the NSCLC were stage I (0%), II (0%), IIIa (0%), IIIb (11.7%) and IV (88.3%). Among 293 lung cancer patients, 89 subjects (30.4%) were diagnosis as pulmonary TB. Two subjects (2.2%) of 89 subjects were truly pulmonary TB while the rest 87 subjects were not pulmonary TB and had ATT for average 12 weeks with the longest period was 16 weeks. The ATT duration >1 month was 76.4%. Conclusions: Percentage of lung cancer patients with ATT before being referred to dr. Moewardi hospital were 30.4% of 293 lung cancer patients while 68 subjects (76.4%) of whom had received ATT >1 month. (J Respir Indo. 2017; 37(4): 288-92)